Analisis Produktivitas Budidaya Tambak Ikan Bandeng Berdasarkan Karakteristik Sosial Ekonomi Pembudidaya di Desa Cangkring, Indramayu - Fuaddin, Taufiq; Handaka Suryana, Asep Agus; Subhan, Ujang; Nurhayati, Atikah (Jurnal Galung Tropika, 2024)
The study was conducted in Cangkring Village, Cantigi District, Indramayu Regency, with respondents who were milkfish farming farmers. The purpose of this study was to analyze the level of productivity of milkfish farming businesses and the relationship between farmers' socio-economic characteristics and productivity. Data was collected using the purposive sampling method and analyzed using quantitative descriptive analysis. The calculation of data analysis used was productivity analysis based on costs and land area and the Pearson product-moment correlation test using SPSS. The results of the productivity analysis per unit area of ??stocking density were 6,602.7 fish/ha/year; for production, the value was 3.31 tons/ha/year, while based on costs, it was Rp—11,407,556.4/ton/year. The results of the Pearson product-moment correlation test analysis of the experience variable had a fragile relationship with productivity, and there was no significant relationship. The analysis results of the variables age, education level, and land area each had a weak relationship with productivity, and only the land area variable had a significant relationship. The analysis results of the stocking density variable had a moderate relationship with productivity, and there was a significant relationship. The analysis results of the variables of business capital and income each have a solid relationship to productivity, and both variables have a significant relationship. The R/C ratio obtained a value of 2.01. It shows that milkfish farming in Cangkring Village has advantages, so it is feasible to run.